2004
DOI: 10.1097/00002030-200411050-00009
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with chronic renal failure in HIV-infected ambulatory patients

Abstract: Our findings suggest that advanced HIV-disease, as indicated by low CD4+ cell count, is associated with subsequently developing chronic renal disease and treatment with HAART may reduce the risk of developing chronic renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 31 publications
5
46
1
Order By: Relevance
“…Only 21 (6%) of the 349 patients with CKD had both risk factors. The association of CD4 cell count and CKD or GFR decline has been found in several studies (23,26,32,33). Interestingly, we found an association between the time spent with a CD4 count of Ͼ200 cells/mm 3 during the last 2 years and a lower risk of CKD.…”
Section: Discussionsupporting
confidence: 77%
“…Only 21 (6%) of the 349 patients with CKD had both risk factors. The association of CD4 cell count and CKD or GFR decline has been found in several studies (23,26,32,33). Interestingly, we found an association between the time spent with a CD4 count of Ͼ200 cells/mm 3 during the last 2 years and a lower risk of CKD.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies had demonstrated that diabetes plays an important role in kidney disease in the HIV infected patients [3,10,20]. Krawczyk et al in the United States (p=0.259) and Flandre et al in France (p=0.30) did not find an association between diabetes and chronic kidney failure among HIV infected patients [4,18].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 97%
“…had found in France, in 2011, in a study of risk factors for chronic kidney disease in patients infected with HIV-1 that hypertension was associated with chronic kidney failure in these patients (OR=2 39, p<0.01) [4]. Krawczyk et al had found in the United States that taking anti-hypertensive treatment is a factor associated with chronic kidney failure (p=0.004) [18]. It's important to note also that hypertension is one of the criteria used by the Infectious Diseases Society of America (IDSA) to describe HIV patients with a high risk of developing kidney disease [19].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 99%
“…Highly active anti-retroviral therapy (HAART) treatment has not eliminated HIV-specific renal disease, the HIV-associated nephropathy (HIVAN), which is responsible for 40% to 60% of the histological renal disease (191), or the need for transplantation in HIV-infected patients (192). Apart from the specific role of the virus, people infected with HIV have a large number of risk factors for non-specific CRF, including age, hypertension, non-insulin-dependent diabetes and exposure to multiple long-term drug treatments (193).…”
Section: Cysc and Acquired Immunodeficiency Syndrome (Aids)mentioning
confidence: 99%